The Design of 3D Virtual Reality Animation of Javan Rhino for Educational Media of Endangered Animals in Indonesia - Kent Vin Lievianto; Yana Erlyana (Teknika, 2024)
Indonesia is one of the largest archipelagic countries in the world. Indonesia has very rich biodiversity but is facing serious threats. Many endemic species are threatened with extinction due to factors such as climate change, habitat loss, illegal trade and poaching. This research highlights the urgent need for education about endangered animals, with a focus on the Javan Rhinoceros (Rhinoceros Sondaicus) which is categorized as Critically Endangered by the International Union for Conservation of Nature (IUCN). This research was created for Animalium, a research facility under the National Research and Innovation Agency (BRIN), which still lacks interactive Virtual Reality media for education. The main aim of this research is to design a 3D VR animation about the Javan Rhino to increase education and awareness about its conservation. Interviews with educators at Animalium revealed the need for such a medium to prevent damage to physical replicas and to engage visitors, especially children, in a more immersive and interactive learning experience. Observations showed that there were no 3D VR-based educational tools in the facility. The implementation of VR technology has the potential to significantly increase visitor engagement and experiences regarding the conservation of endangered species, in line with Sustainable Development Goals (SDGs) related to terrestrial ecosystems. This research highlights the potential of VR to provide immersive and interactive educational experiences, increase public awareness, and support wildlife conservation efforts, especially the Javan Rhino. The result of this design is an Unreal Engine project file that can be used in Animalium to create an immersive and interactive educational experience, increase public awareness, and support wildlife conservation efforts, especially the Javan Rhino.